ANALISA PENGARUH WAKTU PENAHANAN PADA PROSES PACK CARBURIZING TERHADAP KEKERASAN BAJA KARBON RENDAH ST 37 - Apriatun, Apriatun; Taufikurahman, Taufikurahman; Sundari, Ella (Politeknik Negeri Sriwijaya, Indonesia, 2021)
This study aims to analyze the hardness of low carbon steel ST 37 which received pack carburizing treatment with coconut shell charcoal. In this study, the specimens were divided into ten parts, which is five specimens carried out by pack carburizing, and other five parts by pack carburing and hardening and quenching followed by with oil. The carbon medium was coconut shell charcoal with a percentage of 10.60% volatile, 76.32% carbon, 13.08% ash and CaCO3 as a catalyst. The pack carburizing process is carried out at temperature of 9500C with i holding time of 2 hours, 4 hours, 6 hours, 8 hours, and 10 hours, as the oil quenching media hardness testing is carried out to determine how hard the specimen surface is. And the remit are this research was conducted at the material testing laboratory, Department of Mechanical Engineering, Sriwijaya State Polytechnic.